ISLAMIC EDUCATION PARADIGM REGARDING CHILD-FRIENDLY LEARNING WITH THE CONCEPT OF INDEPENDENT LEARNING - Firman Mansir (AULADUNA: Jurnal Pendidikan Dasar Islam, 2022)
Abstract From the pre-colonial era until now, education is a right and obligation for everyone. Education and independence are always related to one another. In Indonesia, everyone is given the freedom to determine for themselves what kind of education they want. This research explained the importance of preparing and designing education for children through the freedom to be creative and innovative with the concept of independent learning following Islamic values. This study used qualitative approach in the form of descriptive-analytic analysis. Data were collected from various literature and then analyzed by interpreting the meaning of the data. The study results indicated that the concept of Freedom to Learn was one of the references in creating superior and quality students. The most important thing about Freedom of Learning felt by every level of education, such as elementary, middle and even tertiary level, was creativity in learning activities so that the educational process became superior and independent.